Optimum Tariffs and Exhaustible Resources: Theory and Evidence for Gasoline - Julien Daubanes; Lisa Leinert (ETH Zurich, CER-ETH - Center of Economic Research, 2012)
Domestic consumption taxes on oil products largely differ across countries, ranging from very high subsidies to very high taxes. The empirical literature on the issue has highlighted the role of revenue-raising (Ramsey commodity taxation) and externalitycorrection (Pigovian taxation) motives for national taxation. Isolatedly, the theoretical literature on non-renewable-resource taxation has emphasized the role of the optimumtariff dimension of excise taxes which reflects countries' non-cooperative exercise of their market power. This paper reconciles these two strands by comprehensively addressing the issue. First, we propose a multi-country model of national taxation with oil – modeled as a polluting exhaustible resource – and some regular commodities. Domestic welfare is maximized with respect to domestic taxes under a revenue-collection constraint. The optimal domestic tax on oil consumption not only consists of a Ramsey inverse-elasticity term and of a Pigovian term, but also of an optimum-tariff component. In fact, resource exhaustibility implies a form of supply inelasticity that magnifies optimum-tariff arguments. Second, based on a multiple regression using a data set with a large number of countries, we test the power of the optimum-tariff tax component in explaining national gasoline taxes. We find strong evidence that this component plays a crucial role in countries' taxation of gasoline.
Keywords: Q38; F12; H20; H70; 330; Non-renewable resources; Domestic taxation; Ramsey taxation; Optimum tariff theory; Gasoline; Mineralölsteuer; Optimale Besteuerung; Internalisierung externer Effekte; Mehr-Länder-Modell; Theorie